FOOD SECURITY AND ITS GLOBAL INSTITUTIONALIZATION - D. Petkov (Trakia Journal of Sciences)
The present manuscript tackles important problems arising during the institutionalization of activities that address the food crisis at the global, regional and national level. Current priorities and principles of the interaction of models for efficient management are derived. Specific features of developing modern conceptual attitudes based on the understanding that food security has a high socio-cultural value have been examined.